(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Lead contamination is an ancient health problem that requires advanced treatment strategies. Here, we review the bioremediation of lead by bacteria, biosorption, exogenous sugars, bioaccumulation, biomineralization and bioaccumulation. The response of bacteria is determined at the molecular level through the expression of specific genes and proteins to combat lead toxicity. Biosorption and biodeposition can be successfully used to clean polluted environments. Bacterial bioremediation can be combined with phytoremediation for a more effective biological treatment. The bioremediation of bacterial lead is limited by environmental conditions, nutrient availability, and the presence of other contaminants from bacterial growth.